ANALYSIS OF DIFFERENCES OF STUDENT LEARNING METHODS BETWEEN REGULAR AND SHORT SEMESTERS (International Journal of Psychosocial Rehabilitation, 2020)
Mastery of lecture material for one semester running for students majoring in management is a necessity in raising the cumulative achievement index. In its implementation, students often feel it is better to take a course in a short semester on the grounds that the teaching lecturer is more generous in giving grades. The purpose of this study is to find out and analyze the differences in the final grades of students of a course will be the same both in the regular semester and short semester. This research is a quantitative descriptive study with a population of students majoring in management in the fourth semester. The sample was selected by purposive sampling of 36 people based on the number of students in the class studied. The research method used is descriptive analysis using different tests. The results of the analysis of the differences show that the relationship between the final grades of courses in the regular semester and in the short semester is weak and the assumption that the final value of a course in the short semester will be higher than that in the regular semester is proven. Final grades of a course in the regular semester and in the short semester are different because the learning process in the short semester is faster and requires students to be more active in learning.